Induction transient liquid phase bonding of Inconel 718 with the nickel-based sintered brazing preform - Yan, Guangxu (2021)
Generally, transient liquid phase (TLP) bonding is conducted with an overdose of filler metal in a vacuum furnace that necessitates excessive post machining. Recently, a new form of filler metal, the sintered brazing preforms (SBP) has been introduced to achieve a neat TLP bonding joint, which undergoes partial melting and retains its original shape. This paper studies the microstructure and mechanical properties of induction TLP bonding (IB) of the Inconel 718 using nickel-based SBP. Firstly, the surface roughness effect on the tensile bonding strength of the brazed joint was investigated. Further, a comparative study between IB and furnace TLP bonding (FB) on the microstructure and mechanical properties of the TLP joints was performed. The results clearly show that neat bonding joints can be obtained through the IB of Inconel 718 using nickel-based SBP. Besides, the strongest tensile bonding strength (240.76 MPa) of the SBP joint after IB was achieved with an optimal bonding surface roughness of around 0.9 μm (Ra). The strength was approximately 16% higher than that of the SBP joint after FB. Furthermore, the IB could accelerate the diffusion process, leading to fewer porosities and borides in the SBP, and a lesser amount of precipitates in the precipitation layer than that after FB.